Teaching reading skills in a foreign language - Nuttall, Christine (Heinemann, 1996)
A revised edition of Christine Nuttall's established text on the teaching of reading skills in a foreign language. It examines the skills required to read effectively and suggests classroom strategies for developing them. A new chapter on testing reading is provided by Charles Alderson